Effect of supplementation of Moringa leaf powder (Moringa oleifera) on growth and production performance of chicken under organic management system. - Goswami, Durga Shankar; MEENA, J P; GUPTA, LOKESH; Goswami, Durga Shankar; Choudhary, Jagdish Lal; Mishra, Shidhartha; Bagri, Dheeraj Kumar (The Indian Journal of Animal Sciences, 2022)
The present study was carried out at poultry farm of Rajasthan College of Agriculture, Maharana Pratap University of Agriculture and Technology, Udaipur for a period of 22 weeks (18 to 40 weeks) for egg production. The objective of the study was to find out the optimum inclusion level of moringa leaf powder (MLP) in poultry diet and study the effect on production performance and economics of Pratapdhan chicken under organic management system. The dietary treatments consisted of the basal diet as control (T1), Feed of organic origin (T2), T2+Moringa Leaf Powder @ 2.5% (T3), T2+Moringa Leaf Powder @ 5% (T4), T2+Moringa Leaf Powder @ 7.5% (T5) and T2+Moringa leaf powder @ 10%. The bodyweight of chicken ranged between 1259.75 g to 1425.67 g in different treatments at 22 weeks of age whereas at 32 weeks of age the bodyweights were significantly higher in T3 and lowest in T5 group. The feed intake among different treatment groups was found to be non-significant. The hen day egg production was maximum in T4 at 56.91 eggs and T5 at 56.32 as compared to the rest of the treatments.